TPACK-Based Learning Management Training at PEKERTI Batch 3, Bengkulu University in 2024 - Risdianto, Eko; Coastera, Funny Farady; Gushevinalti, Gushevinalti; Chandra, Muhammad Fiqih Rizqi; Macariola, Juli Simon; Farooque, Sm (CV Media Inti Teknologi, 2024)
Most lecturers have difficulty adapting to technological advances, including in implementing the TPACK (Technological Pedagogical Content Knowledge) framework. Therefore, one solution is to hold training packaged in a program called the PEKERTI Program (Basic Instructional Engineering Skills Improvement). The 2024 Batch 3 PEKERTI program at Bengkulu University was implemented with the aim of training lecturers in carrying out TPACK-based learning management. This activity, which was held in January 2024, was attended by 39 lecturers. A closed questionnaire with 4 answer choices was used as a research tool. Descriptive statistical analysis is the data analysis method used. PEKERTI participants' answers to the implementation of the training were analyzed using data collected in the form of percentages which were the results of calculations using a modified Likert Scale. The research results show that 100% of respondents are in the Strongly Agree category based on the guidelines in table 4 of the Likert scale interpretation. Meanwhile, for the agree, disagree and strongly disagree categories, there were 0 respondents. So, it can be concluded that the TPACK-based learning management training for Pekerti Batch 3 in 2024 at Bengkulu University received a positive response from participants.